Implicit Theories of Creativity in Higher Education: A Constructivist Study. Issue 3 (3rd July 2019) - Pavlović, Jelena; Maksić, Slavica
Abstract : A qualitative constructivist study was conducted to explore university teachers' implicit theories of creativity. The aim of the study was to understand how university teachers (NL = 46) define creativity and perceive its manifestations and development. University teachers' conceptions of creativity were elicited using the Implicit Theories of Creativity Questionnaire (ITC-Q). The qualitative analysis resulted in five types of implicit theories of creativity and its development: individualistic theories, activity theories, result-oriented theories, relational theories, and growth theories. By including a new theoretical position, target group, and a methodological framework, the study broadened the dialogue about creativity and its development in higher education.